Evidence review of smallholder adaptation to climate change - Knox, Jerry W. (Cranfield University, 2021)
The aim of this IFAD funded systematic review was to assess the extent to which learning outcomes have supported initiatives to mainstream adaptation for smallholder agriculture, focussing on three key areas, (i) scaling up climate sensitive adaptive interventions, (ii) the role of knowledge management to promote effective adaptive solutions, and (iii) human-ecosystem interactions in climate change adaptation. The dataset provides a summary of the evidence identified as part of the bibliographic searches and the analyses that were then conducted on the screened data.
Keywords: smallholder farming systems'; 'Climate Change Evidence'; 'Agriculture'; 'adaptation measures'; 'Agricultural Land Management'; 'Farm Management; Rural Management and Agribusiness'; 'Farming Systems Research'; 'Sustainable Agricultural Development'